2022
DOI: 10.3390/vaccines10101685
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Switching Mycophenolic Acid to Sirolimus on Serological Response after a SARS-CoV-2 Booster Dose among Kidney Transplant Recipients: A Pilot Study

Abstract: Kidney transplant recipients (KTRs) have a suboptimal immune response to COVID-19 vaccination due to the effects of immunosuppression, mostly mycophenolic acid (MPA). This study investigated the benefits of switching from the standard immunosuppressive regimen (tacrolimus (TAC), MPA, and prednisolone) to a regimen of mammalian target of rapamycin inhibitor (mTORi), TAC and prednisolone two weeks pre- and two weeks post-BNT162b2 booster vaccination. A single-center, opened-label pilot study was conducted in KTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For instance, Cheng et al reported that the neutralizing antibody responses to a SARS-CoV-2 vaccine were unchanged in sirolimus-treated lymphangioleiomyomatosis patients, suggesting that monotherapy with sirolimus or other mTOR inhibitors does not prevent antibody responses to SARS-CoV-2 vaccines [40]. In other studies, a positive, beneficial effect of sirolimus and mTOR inhibitors on anti-SARS-CoV-2 antibody production was reported [24,41,42]. For instance, an immunosuppressive regimen based on low doses of the mTOR inhibitor everolimus was found by de Boer et al to be associated with a higher humoral response rate after COVID-19 vaccination in elderly kidney transplant recipients [42].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Cheng et al reported that the neutralizing antibody responses to a SARS-CoV-2 vaccine were unchanged in sirolimus-treated lymphangioleiomyomatosis patients, suggesting that monotherapy with sirolimus or other mTOR inhibitors does not prevent antibody responses to SARS-CoV-2 vaccines [40]. In other studies, a positive, beneficial effect of sirolimus and mTOR inhibitors on anti-SARS-CoV-2 antibody production was reported [24,41,42]. For instance, an immunosuppressive regimen based on low doses of the mTOR inhibitor everolimus was found by de Boer et al to be associated with a higher humoral response rate after COVID-19 vaccination in elderly kidney transplant recipients [42].…”
Section: Discussionmentioning
confidence: 99%